2001
DOI: 10.1055/s-2001-10894
|View full text |Cite
|
Sign up to set email alerts
|

Vergleich zwischen 3D-Power-Doppler-Ultraschall, farbkodierte Duplexsonographie und digitaler Subtraktionsangiographie bei Karotisstenosen

Abstract: Even in cases with severe atherosclerosis, both sonographic methods reveal similar results comparable to DSA. 3D PDUS does not result in a diagnostic improvement on CDUS, however, it does give the new opportunity for complete data storage, reconstruction, and survey presentations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
0
4
1
1
Order By: Relevance
“…Still, our value of the CTA specificity was lower, when compared with that reported by other authors - Anderson et al (2000) (up to 92%), Leclerc et al (1999) and Marcus et al (1999) (up to 96%), Mildenberger et al (1997) and Alvarez-Linera et al (2003) (up to 98%) and 100% published by Simeone et al (1997), Sameshima et al (1999), Randoux et al (2001) and Patel et al (2002). Our low US specificity was worse than the results of the majority of other studies (83-98%; Steinke et al, 1990;Moneta et al, 1993;Faught et al, 1994;Neale et al, 1994;Barnett et al, 1996;Hood et al, 1996;Guo et al, 2000;Huston et al, 2000;Lovrencˇic´-Huzjan et al, 2000;Dinkel et al, 2001;Keberle et al, 2001;Rotstein et al, 2002), however, it was better when compared with the other ones (46-74% - Browman et al, 1995;Steinke et al, 1997;Anderson et al, 2000;Back et al, 2000;Johnston and Goldstein, 2001;New et al, 2001;Patel et al, 2002).…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Still, our value of the CTA specificity was lower, when compared with that reported by other authors - Anderson et al (2000) (up to 92%), Leclerc et al (1999) and Marcus et al (1999) (up to 96%), Mildenberger et al (1997) and Alvarez-Linera et al (2003) (up to 98%) and 100% published by Simeone et al (1997), Sameshima et al (1999), Randoux et al (2001) and Patel et al (2002). Our low US specificity was worse than the results of the majority of other studies (83-98%; Steinke et al, 1990;Moneta et al, 1993;Faught et al, 1994;Neale et al, 1994;Barnett et al, 1996;Hood et al, 1996;Guo et al, 2000;Huston et al, 2000;Lovrencˇic´-Huzjan et al, 2000;Dinkel et al, 2001;Keberle et al, 2001;Rotstein et al, 2002), however, it was better when compared with the other ones (46-74% - Browman et al, 1995;Steinke et al, 1997;Anderson et al, 2000;Back et al, 2000;Johnston and Goldstein, 2001;New et al, 2001;Patel et al, 2002).…”
Section: Discussioncontrasting
confidence: 51%
“…This is a very good result, when compared with some other studies, which focused on the diagnostics of such stenoses. The values of the US sensitivity reported in the literature ranged from 65 to 98% (Moneta et al, 1993;Faught et al, 1994;Neale et al, 1994;Browman et al, 1995;Barnett et al, 1996;Hood et al, 1996;Anderson et al, 2000;Back et al, 2000;Guo et al, 2000;Huston et al, 2000;Lovrencˇic´-Huzjan et al, 2000;Dinkel et al, 2001;Johnston and Goldstein, 2001;New et al, 2001;Patel et al, 2002); Demarin et al (1989), Steinke et al (1990Steinke et al ( , 1997, Keberle et al (2001) and Rotstein et al (2002) also reported 100% US sensitivity in their studies. Our 100% CTA sensitivity was superior to the results in most of the studies, in which the values ranged from 65 to 95% in severe stenoses (Cumming and Morrow, 1994;Mildenberger et al, 1997;Simeone et al, 1997;Magarelli et al, 1998;Sugahara et al, 1998;Marcus et al, 1999;Sameshima et al, 1999;Anderson et al, 2000;Patel et al, 2002;Alvarez-Linera et al, 2003); only Leclerc et al (1999) and Randoux et al (2001) also reported 100% sensitivity.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Accuracy of DUS compared with digital subtraction angiography (DSA) was studied in several studies. Keberle [ 4 ] compared DUS and DSA in the assessment of ICA stenosis in patients with severe atherosclerosis; the correlation between the 2 techniques was 97% (r=0.97; P<0.001). The sensitivity and specificity in the detection of high-degree stenosis were 100% and 93.3%, respectively [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Durch die fehlende Gefäûwandüberzeichnung ermöglicht der B-Flow eine artefaktfreiere Darstellung des prä-, intra-und poststenotischen Flusses und erleichtert damit die Beurteilung des distalen Stenosegrades. Da der B-Flow aber keine Geschwindigkeitsbestimmung ermöglicht, bleibt die Beurteilung der hämodynami-schen Flussparameter der FKDS vorbehalten[30].Durch Weiterentwicklungen sind im Power Mode teilweise 3D-Darstellungen der Flussphänomene möglich, die das Ausmaû einer hochgradigen Stenose verdeutlichen[14]. Dabei erschweren aber ausgeprägte, insbesondere zirkuläre Verkalkungen ein Kinking oder eine deutliche Elongation, sowie eine hohe Bifurkation generell die sonographische Beurteilung des Stenosegrades der A. carotis interna.…”
unclassified